Investigation of internal forces of knee during hiking with Anybody software. - Toh, Jared Jun Yong. (2011)
Sailing is a vigorous and dynamic sport that requires precise techniques and superior physical fitness. During upwind sailing, the aerodynamics forces acting on the sail will cause the deck to heel - the stronger the wind and the higher the sailing angle to the wind, the greater the heeling force. Water currents and waves can also contribute to the heeling force. Sailors perform many sporadic and sudden body movements to counteract these forces and prevent the vessel from capsizing. Such movements, together with poor hiking technique and insufficient physical strength can cause severe injuries to the spine and knees. Numerous studies have quantified the occurrence of injuries during sailing. According to a review by Moraes et al , most injuries occurred in the lower back (52.9%), followed by other back areas (41.2%), knees (25–32%), right thigh (26.5%), neck (23.5%), right shoulder (23.5%), and forearm or elbow (20.6%). Another study by Legg et al (1997) revealed that 57% of New Zealand Olympic sailors reported injury in the preceding three years, including the lower back (45%), knee (22%), shoulders (18%), and arms (15%).